Relationships Between Working From Home, Sitting Postures, and Low Back Pain During COVID-19: A Survey of Frequent Computer Users. - Snodgrass, Suzanne J.; Kang, Chris J. W.; Edwards, Suzi; Heneghan, Nicola R.; Puentedura, Emilio J.; James, Carole (Journal of Occupational & Environmental Medicine, 2024)
In computer workers predominantly using a home or hybrid work environment, self-reported sitting posture and depressive symptoms were associated with low back pain. However, the location of work was not associated with pain. Thus, sitting posture and depression may be important factors to consider alongside workstation ergonomics. Objective: The aim of the study is to investigate the effects of working from home on musculoskeletal pain. Methods: An e-survey of computer workers was conducted. Multinomial logistic regression modeling examined relationships between work location (work or home office desk, dining table, other), sitting posture (diagrams with descriptors), depressive symptoms (Center for Epidemiologic Studies Short Depression Scale), sleep quality (good/average vs poor) and pain (low back pain [LBP]), and other pain without LBP (asymptomatic). Results: Of 634 respondents, most (91%, n = 578) worked partially at home and had pain (91%, n = 576; 342 LBP, 234 other pain, 58 asymptomatic). Sitting posture ("trunk a little bent forward" vs "straight up, back against back rest": odds ratio = 2.9; 95% confidence interval = 1.3–6.5, P = 0.008), being female (2.2; 1.2–4.1, P = 0.008), and depressive symptoms (3.4; 1.7–6.6; P < 0.001) were associated with LBP. Poor sleep quality related to LBP but correlated with depressive symptoms. Working from home and location were not associated with pain. Conclusions: Sitting postures, but not working from home, are associated with LBP.